Pratiques orthographiques en français d’étudiants étrangers: le cas d’étudiants hispano-américains et afghans - Gonac'h, Jeanne; Mortamet, Clara (My University, 2011)
In this article, we analyze and compare French spelling errors produced by two different groups of university students who have learned French in a country where French is a foreign language (FFL): students from Central and South American countries (Salvador, Peru and Argentine) and Afghanistan. Our corpus is based on errors found in papers of graduate distance-learning students, most of whom are planning on becoming French teachers in their countries. Our aim is to identify what errors are specific to FFL university students and eventually what errors are specific to the two different groups. The first results of our study confirm tendencies observed on previous research and prove that there exist specific types of errors for FFL learners. In the end, we will also discuss the limit of error categories.